Migraine and Mortality: A Systematic Review and Meta-Analysis - Schürks, Markus (2011)
OBJECTIVE: To evaluate the evidence on the association between migraine and mortality. METHODS: Systematic review and meta-analysis of studies investigating the association between any migraine (all forms of migraine collectively) or migraine subtypes (e.g. migraine with aura) and mortality published until March 2011. RESULTS: We identified ten cohort studies. Studies differed regarding the types of mortality investigated and only four presented aura-stratified results, limiting pooled analyses for migraine subtypes and cause-specific mortality. For any migraine pooled analysis does not suggest an association with all-cause (five studies; pooled relative risk [RR]=0.90, 95%CI 0.71–1.16), cardiovascular (CVD; six studies; pooled RR=1.09, 95%CI 0.89–1.32), or coronary heart disease mortality (CHD; three studies; pooled RR=0.95, 95%CI 0.57–1.60). Heterogeneity among studies is moderate to high. Two studies each suggest that migraine with aura increases risk for CVD and CHD mortality. CONCLUSION: This meta-analysis does not suggest that any migraine is associated with mortality from all-causes, CVD, or CHD. However, there is heterogeneity among studies and suggestion that migraine with aura increases CVD and CHD mortality. Given the high migraine prevalence a definitive answer to the question if migraine or a subtype alters risk for mortality is of high public health importance; hence, further studies are needed.